Gold surface anticoagulant coating structure as well as preparation method and application thereof

By constructing micro-nanomorphology on the surface of the gold layer and modifying fluorothiol, lubricant is injected into a porous self-lubricating surface, solving the problem of easy depletion of lubricating fluid in the liquid injection surface method, and achieving a long-lasting anticoagulation effect .

CN119424767AActive Publication Date: 2025-02-14BEIJING UNIV OF CHEM TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411500185.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-14
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

When the surface of the material is subjected to anticoagulation treatment by using the liquid injection surface, the injected lubricating liquid is easily depleted, resulting in failure of anticoagulation performance and poor durability.

Method used

Micro-nanomorphology is constructed by in-situ wet chemical reduction of chloroaulic acid on the surface of the gold layer, and the surface of the micro-nano gold layer is modified by fluorothiol, and the lubricant is injected into the modified micro-nano gold surface to construct porous self-lubricating Surface (SLIPS).

Benefits of technology

It significantly improves the locking ability of the lubricant, making it less likely to be lost, maintains a long-lasting anticoagulant function, and improves the stability and durability of anticoagulant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424767A_ABST
    Figure CN119424767A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of medical precious metal materials and medical instruments, in particular to a gold surface anticoagulation coating structure and a preparation method and application thereof. According to the method, a micro-nano morphology surface is constructed on the surface of a gold layer through in-situ wet chemical reduction of chloroauric acid, the surface of the micro-nano gold layer is modified through fluoromercaptan, a lubricating agent is injected into the modified micro-nano gold surface, and a lubricating agent injected porous self-lubricating surface (SLIPS) is constructed; the locking capacity of the surface of the nano-gold layer modified by fluoromercaptan to the lubricating layer is remarkably improved, so that the lubricating layer is not prone to loss, and the long-lasting anticoagulation function is achieved. The problems that when a liquid injection surface method is adopted for conducting anticoagulation treatment on the surface of a material, injected lubricating liquid is prone to being exhausted, and the anticoagulation performance durability is poor are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical precious metal materials and medical devices, and more particularly to a gold surface anticoagulation coating structure and a preparation method and application thereof. Background Art

[0002] Blood-contact medical devices are widely used in the treatment of cardiovascular diseases and have saved countless lives. Blood-contact medical devices include implants in the body (such as central venous catheters and coronary stents), components of extracorporeal life support systems (such as dialysis circuits and extracorporeal membrane oxygenator (ECMO) circuits), and other materials in contact with blood (such as materials used for blood collection and storage). However, due to the poor blood compatibility and weak surface anticoagulant properties of blood-contact medical devices, they are often prone to triggering endogenous coagulation cascade reactions, leading to thrombosis, inflammatory reactions and bacterial infections, causing medical device failure. What is more serious is that thrombi may enter important organs such as the lungs and brain through blood circulation, causing vascular and pulmonary embolism, and then triggering a series of complications, which not only significantly increase treatment costs, but may also pose a serious threat to patients' lives.

[0003] Blood coagulation on the surface of blood-contact medical devices starts with protein adsorption. The protein layer formed on the surface of the material further induces platelet adhesion, activation and aggregation, activating the coagulation cascade reaction to form thrombi. Therefore, surface modification strategies that minimize the nonspecific adhesion of proteins and cells to modify the surface of blood-contact medical devices are the most effective way to reduce coagulation on the surface of materials. Surface modification is to resist coagulation and activation of the immune system by changing the blood-material interface, which can be divided into physical and chemical methods and surface biofunctionalization. Surface biofunctionalization gives the surface the ability to actively interfere with thrombin and coagulation factors, such as endothelialized surfaces, heparinized surfaces, and NO-releasing surfaces. Physical and chemical methods are to change the surface morphology, charge, and hydrophilicity / hydrophobicity of the material at the nanoscale to affect the interaction between the material surface and proteins, platelets, etc. in the blood to inhibit the formation of thrombi, such as hydrophobic surfaces, patterned surfaces, liquid-injected surfaces, hydrogel-based surfaces, etc.

[0004] Liquid-infused surfaces (LIS) can effectively repel different types of liquids, such as water, hydrocarbons, crude oil, and blood, by injecting a layer of viscous liquid on the surface to form a smooth interface. At the same time, the surface can maintain low contact angle hysteresis and quickly restore its drainage characteristics after physical damage. This technology shows broad application prospects in medical and marine applications in terms of anti-biological contamination, reducing friction resistance, and preventing ice formation. Inspired by pitcher plants, Joanna Aizenberg's team designed a liquid-injected porous surface in 2011, using a micro-nanostructured matrix to fix the injected lubricant and successfully prepared a lubricating layer with long-term stability. This smooth surface injected with liquid shows better compressive resistance than superhydrophobic surfaces. However, the injected liquid is easy to lose, so there are still certain shortcomings in durability. Summary of the invention

[0005] The technical problem solved by the present invention is that when the material surface is treated with anticoagulation by liquid injection, the injected lubricating liquid is easily exhausted, resulting in failure of its anticoagulation performance; that is, the durability of the anticoagulation performance is poor.

[0006] The present invention utilizes chloroauric acid to perform in-situ wet chemical reduction on the surface of a gold layer to construct a micro-nano morphology, adopts fluorothiol to modify the surface of the micro-nano gold layer, injects a lubricant into the modified micro-nano gold surface, and constructs a porous self-lubricating surface (SLIPS); the micro-nano gold layer surface modified with fluorothiol has a significantly improved locking ability for the lubricant, so that the lubricant is not easily lost, thereby having a lasting anti-coagulation function.

[0007] One of the purposes of the present invention is to provide a gold surface anti-coagulation coating structure.

[0008] The gold surface anti-coagulation coating structure comprises, from bottom to top, a micro-nano gold surface, a grafted modification layer and an anti-coagulation layer.

[0009] The grafted modification layer contains fluorine-containing thiol, which is grafted on the surface of micro-nano gold. The fluorine-containing thiol has a thiol functional group, which can react with the gold surface to form a gold-sulfur covalent bond; the fluorine-containing thiol is grafted on the surface of the micro-nano gold through the gold-sulfur interaction, and a fluorine-containing film is firmly formed on the surface of the micro-nano gold.

[0010] The fluorine-containing mercaptan is selected from one or more of 1H, 1H, 2H, 2H-perfluorodecanethiol, 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluoro-1-octanethiol, and 3,3,4,4,5,5,6,5,6-n-fluoro-1-hexanethiol; preferably 1H, 1H, 2H, 2H-perfluorodecanethiol.

[0011] The anticoagulation layer contains a lubricant. Specifically, the anticoagulation layer is formed by a lubricant. The lubricant can be selected from one or more of perfluoropolyether, silicone oil, fluorinated lubricating oil, ionic liquid, and polyethylene glycol.

[0012] The grafted modified layer is a fluorine-containing film grafted on the surface of micro-nano gold through a gold-sulfur covalent bond. Compared with the three-dimensional network structure of the polymer, although the storage capacity of the fluorine-containing film is limited, the fluorine-containing film and the lubricant can maintain strong mutual adsorption through low surface energy, thereby adsorbing the lubricant on the surface of the micro-nano gold, so that the lubricant is less lost during use, or even does not lose. It can be seen that the fluorine-containing thiol grafted modified layer is firmly grafted on the surface of the micro-nano gold through the gold-sulfur interaction on the one hand, and on the other hand, the lubricant is strongly adsorbed through low surface energy, so that the lubricant is firmly attached to the surface of the micro-nano gold, solving the problem of easy loss of lubricants and poor durability of anti-coagulation effect.

[0013] When the lubricant contains fluorine, the fluorine-containing thiol in the grafted modified layer and the fluorine-containing lubricant can also maintain the adhesion of the lubricant through fluorine-fluorine interaction, thereby further improving the adhesion of the lubricant on the surface of the micro-nano gold. Therefore, as a preferred embodiment, the lubricant is a fluorine-containing lubricant, more preferably a perfluoropolyether.

[0014] The present invention constructs a micro-nano morphology by an in-situ wet chemical reduction reaction of chloroauric acid on the surface of a gold-plated layer, utilizes the gold-sulfur interaction to graft fluorinated mercaptan on the surface of the micro-nano gold layer, and injects a lubricant into the modified micro-nano gold surface to construct a porous self-lubricating surface (SLIPS), which can greatly reduce the resistance to blood flow and play an effect of resisting blood adhesion. By preparing a micro-nano gold surface, utilizing the affinity of fluorinated mercaptan to the lubricant and the strong interaction of gold-sulfur, the locking ability of the gold surface to the lubricant is greatly increased, and it has a lasting anticoagulant performance. Compared with the current anticoagulant measures, the present invention improves the locking ability of the lubricating layer by utilizing the capillary action of the micro-nano structure surface and the affinity of the surface-grafted fluorinated mercaptan to the lubricant.

[0015] The second object of the present invention is to provide a method for preparing the gold surface anti-coagulation coating structure described in the first object of the present invention.

[0016] The method for preparing the gold surface anticoagulation coating structure comprises:

[0017] (1) Coating the gold surface with chloroauric acid solution to obtain a micro-nano gold surface;

[0018] (2) coating a fluorine-containing thiol solution on the surface of the micro-nano gold, allowing it to stand, and drying it to form a grafted modification layer;

[0019] (3) placing the micro-nano gold surface containing the grafted modification layer in a lubricant, soaking it, taking it out, and placing it vertically to form an anti-coagulation layer.

[0020] In step (1), after the chloroauric acid solution is applied to the gold surface, the chloroauric acid in the chloroauric acid solution and the gold surface undergo a rapid redox reaction, and the chloroauric acid is in situ wet chemically reduced on the surface of the gold-plated layer to construct a micro-nano morphology surface, thereby obtaining a micro-nano gold surface. Specifically, the chloroauric acid solution is applied to the gold surface and allowed to stand for 10 minutes to obtain a micro-nano gold surface.

[0021] In step (1), the coating can be performed by a conventional coating method in the art. Specifically, a certain amount of chloroauric acid solution can be added to the gold surface with a pipette, and then spread evenly to cover the entire gold surface.

[0022] In step (1), the gold surface may be a surface of metallic gold or a surface of a gold-plated layer based on other materials.

[0023] In step (1), the solvent of the chloroauric acid solution is pure water.

[0024] In step (1), the concentration of the chloroauric acid solution can be selected within a wide range, and the technician can select a suitable chloroauric acid solution concentration according to actual needs. As a preferred embodiment, the concentration of the chloroauric acid solution is 10mM to 100mM, more preferably 50mM to 100mM.

[0025] In step (1), the amount of the chloroauric acid solution can be selected within a wide range, and the technician can select the appropriate amount of chloroauric acid solution according to actual needs. As a preferred embodiment, each 1×1 cm 2 The amount of the chloroauric acid solution on the gold surface is 20 μL to 100 μL, preferably 20 μL to 50 μL.

[0026] In step (2), the solvent of the fluorine-containing thiol solution can be selected from a wide range, and the technician can select a suitable solvent according to actual needs. Preferably, an organic solvent that is easily volatile is selected, for example, it can be selected from anhydrous ethanol, acetone or isopropanol.

[0027] In step (2), the concentration of the fluorine-containing thiol solution can be selected within a wide range, and the technician can select a suitable concentration according to actual needs. Specifically, the concentration of the fluorine-containing thiol solution is 1-5M, preferably 2-3M, for example 2M.

[0028] In step (2), the function of standing is to allow the fluorinated thiol to fully react with gold; the function of drying is to volatilize the solvent in the fluorinated thiol solution and remove the free fluorinated thiol on the surface. The standing time and drying conditions can be selected within a wide range, and technicians can select appropriate standing time and drying conditions according to actual needs. Specifically, the standing time can be more than 12 hours, for example, 12 hours; the drying conditions can be vacuum, room temperature (for example, 25°C), and the drying time can be more than 1 hour, for example, 1 hour.

[0029] In step (3), the role of immersion is to allow the lubricant to fully fill the surface of the grafted modified micro-nano gold structure; "vertical" means that the gold surface is perpendicular to the horizontal plane, and the role of the vertical placement of the gold surface is to remove excess lubricant on the surface. The immersion temperature, immersion time, and vertical placement time can be selected within a wide range, and technicians can select appropriate immersion temperature, immersion time, and vertical placement time according to actual needs. Specifically, the immersion temperature can be 60 to 80°C, for example, 80°C; the immersion time can be more than 48 hours, for example, 48 hours; the vertical placement time can be more than 12 hours, for example, 12 hours.

[0030] The method for preparing the anticoagulant coating structure on the gold surface may further include, before step (1), cleaning the gold surface. The cleaning of the gold surface may be performed by conventional operations. Specifically, it may include: firstly, ultrasonically treating the surface with anhydrous ethanol solution for 10 minutes to wash away grease, dust and other debris; then ultrasonically treating the surface with deionized water for 10 minutes to further wash away the residual ethanol; and finally, using a blast drying oven set at a temperature of 80°C to dry the surface moisture.

[0031] The method for preparing the gold surface anticoagulation coating structure, wherein a specific scheme comprises:

[0032] Step 1: Clean the gold surface: first, use anhydrous ethanol solution to ultrasonically treat the gold surface for 10 minutes to wash away grease, dust and other debris; then use deionized water to ultrasonically treat for 10 minutes to further clean the residual ethanol; finally, use a blast drying oven set at 80°C to dry the surface moisture;

[0033] Step 2, preparing a gold surface modifier: using pure water as solvent to prepare a 10mM to 100mM chloroauric acid solution, using anhydrous ethanol as solvent to prepare a 2M fluorinated thiol solution, both of which are used as gold surface modifiers.

[0034] Step 3, surface treatment: first, add 20 μL to 100 μL of chloroauric acid solution to the cleaned gold surface with a pipette and spread it evenly to cover the gold surface completely, place it at room temperature for 10 minutes, then wash the surface with pure water to prepare a micro-nano gold surface; secondly, apply a layer of fluorine-containing thiol solution on the prepared micro-nano gold surface to cover the gold surface completely, place it at room temperature overnight, react for 12 hours, and then graft the fluorine-containing thiol on the gold surface; then place it in a vacuum oven for 1 hour to remove the free fluorine-containing thiol on the surface of the material;

[0035] Step 4: Oil immersion treatment: Place the surface treated sample in a lubricant in an oven at 80°C for 48 hours;

[0036] Step 5: Oil control treatment: Place the oil-immersion treated sample vertically for 12 hours to remove excess lubricant.

[0037] The third object of the present invention is to provide an application of the gold surface anticoagulation coating structure described in the first object of the invention or the gold surface anticoagulation coating structure prepared by the preparation method described in the second object of the invention in medical devices. Specifically, the application in the field of blood contact medical device materials.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The gold surface anticoagulant coating structure prepared by treating the gold surface in the present invention can prevent the adhesion of proteins and cells, prevent platelet activation, inhibit the coagulation cascade reaction, and has a good anticoagulant effect. Complications caused by the use of anticoagulant drugs can be avoided, and vascular embolism caused by coagulation on the surface of medical devices can be inhibited. Precious metal gold has good biocompatibility and a simple preparation method. It is suitable for the surface treatment of gold-plated medical implants and can be applied to the surface anticoagulant treatment of all precious metal medical devices in contact with blood; it has good application prospects in the field of anticoagulant medical devices and medical implants.

[0040] The invention performs modification treatment on the gold surface and then injects a lubricant. The prepared liquid-injected surface can reduce the resistance of blood flow and play a role in resisting blood adhesion. By preparing a micro-nano gold surface, the affinity of fluorinated thiol to the lubricant and the strong interaction between gold and sulfur are utilized, the locking ability of the gold surface to the lubricant is greatly increased, and the capillary effect of the micro-nano structure of the gold surface on the lubricant is coordinated to enhance the locking ability of the gold surface to the lubricant, and the gold surface has a high-efficiency and lasting anti-coagulation ability, a long-term anti-coagulation effect, and significantly improves the anti-coagulation stability of the gold surface.

[0041] The invention adopts chloroauric acid in-situ reduction to prepare nanoparticles on the gold surface, and the morphology is easy to control, the method is simple, the preparation cost is low, and the equipment requirements are low. The prepared self-lubricating anticoagulant surface has good durability and stability and has a long-term anticoagulant effect.

[0042] In the present invention, the room temperature is 20-30°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1a This is the SEM image before the gold-plated layer is modified;

[0044] Figure 1b This is a SEM image of the surface structure of the micro-nano gold obtained by modification in Example 1;

[0045] Figure 1c This is a SEM image of the surface structure of the micro-nano gold obtained by modification in Example 2;

[0046] Figure 1d This is a SEM image of the surface structure of the micro-nano gold obtained by modification in Example 3;

[0047] Figure 2a This is the AFM two-dimensional morphology image before the gold-plated layer is modified;

[0048] Figure 2b The AFM two-dimensional morphology image of the micro-nano gold surface structure obtained by modification in Example 1;

[0049] Figure 2c The AFM two-dimensional morphology image of the micro-nano gold surface structure obtained by modification in Example 2;

[0050] Figure 2d The AFM two-dimensional morphology image of the micro-nano gold surface structure obtained by modification in Example 3;

[0051] Figure 3a This is the AFM three-dimensional morphology image before the gold-plated layer is modified;

[0052] Figure 3b The AFM three-dimensional morphology of the surface structure of the micro-nano gold obtained by modification in Example 1;

[0053] Figure 3c The AFM three-dimensional morphology of the surface structure of the micro-nano gold obtained by modification in Example 2;

[0054] Figure 3d The AFM three-dimensional morphology image of the micro-nano gold surface structure obtained by modification in Example 3;

[0055] Figure 4a The scanning electron micrographs of platelet adhesion before and after the gold-plating layer was modified;

[0056] Figure 4b The self-lubricating gold surface anti-coagulation coating structure NP obtained by modification in Example 1 50 -Scanning electron microscopy image of platelet adhesion of SLIPS;

[0057] Figure 4c The self-lubricating gold surface anti-coagulation coating structure NP obtained by modification in Example 2 100-20 -Scanning electron microscopy image of platelet adhesion of SLIPS;

[0058] Figure 4d The self-lubricating gold surface anti-coagulation coating structure NP obtained by modification in Example 3 100-50 -Scanning electron microscopy image of platelet adhesion of SLIPS;

[0059] Figures 4a-4d In the figure, the magnification of the scanning electron microscope is 10WX;

[0060] Figure 5 The quantitative analysis results of platelet adhesion before and after gold plating modification; the vertical axis is the adhesion rate; control is the metal plating before modification, NP 50 -SLIPS is a self-lubricating gold surface anti-coagulation coating structure NP obtained by modification in Example 1 50 -SLIPS, NP 100-20 -SLIPS is a self-lubricating gold surface anti-coagulation coating structure obtained by modification in Example 2, NP 100-50 -SLIPS is a self-lubricating gold surface anti-coagulation coating structure NP obtained by modification in Example 3 100-50 -SLIPS;

[0061] Figure 6 It is a schematic diagram of the contact angle stability of the self-lubricating gold surface anti-coagulation coating structure surface at different ultrasonic times obtained by modification of Examples 1-3 and Comparative Example 1, wherein the horizontal axis is the ultrasonic time and the vertical axis is the static water contact angle. DETAILED DESCRIPTION

[0062] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0063] In the following examples and comparative examples, unless otherwise specified, all raw materials and reagents used are commercially available products.

[0064] Chloroauric acid (III) trihydrate (Aladdin, HAuCl4·3H2O, 99.9%), 1H,1H,2H,2H-perfluorodecanethiol (Aladdi, CF3CF 27 CH2CH2SH, Mn = 480.18) were obtained from Aladdin Reagents and used as received.

[0065] Perfluoropolyether (Macklin, Mn=4500) and PBS buffer (PH=7.2-7.4) were purchased from Macklin.

[0066] Sodium citrate (98%, BR) was purchased from Beijing Solebow Technology Co., Ltd.

[0067] The solvent anhydrous ethanol was purchased from Shanghai Myrel Biochemical Technology Co., Ltd. and used as received.

[0068] Example 1

[0069] (1) Clean the gold-plated surface. First, use anhydrous ethanol solution to ultrasonically treat the gold-plated surface for 10 minutes to wash away grease, dust and other impurities; then use deionized water to ultrasonically treat for 10 minutes to further clean the residual ethanol; finally, use a blast drying oven set to 80°C to dry the surface moisture. The morphology of the gold-plated layer after cleaning (SEM, 2D AFM, 3D AFM) is shown below: Figure 1a , Figure 2a , Figure 3a As shown; Figure 1a , Figure 2a , Figure 3a It shows that the surface roughness of the unmodified gold-plated layer is relatively low, and its arithmetic average roughness (Arithmetic Average Roughness, referred to as Ra) Ra = 22.2nm.

[0070] (2) Prepare gold surface modifiers. Use pure water as solvent to prepare 50mM and 100mM chloroauric acid solutions; use anhydrous ethanol as solvent to prepare 2M fluorinated thiol solution; both are used as gold surface modifiers.

[0071] (3) Take 20 μL of 50 mM chloroauric acid solution and apply it to 1×1 cm 2 After cleaning, the gold-plated surface is 1×1cm 2 The gold-plated surface was completely covered and placed at room temperature for 10 minutes to fully perform in-situ reduction of chloroauric acid to form a micro-nano gold surface. The morphology of the micro-nano gold surface (SEM, two-dimensional AFM, and three-dimensional AFM) are shown in Figure 2. Figure 1b , Figure 2b , Figure 3b shown. Figure 1b , Figure 2b , Figure 3b It is shown that after the gold-plated layer is modified in this step, its surface roughness is improved, and its arithmetic average roughness Ra = 54.2nm. After the gold-plated layer is modified in this step, a saline-alkali surface coating is formed, forming a uniform and dense gold nanoparticle coating at the micro-nano level.

[0072] (4) In 1×1cm 220 μL of fluorinated thiol solution was applied on the surface of saline-alkali land-shaped micro-nano-gold to form a fluorinated thiol modified layer.

[0073] (5) In an environment of 80°C, perfluoropolyether was injected into a 1×1 cm 2 The saline-alkali-alkaline micro-nano gold surface with a fluorinated thiol modified layer was placed for 48 hours, and then the gold surface was placed vertically to the horizontal plane for 12 hours to remove the excess perfluoropolyether, thereby obtaining a self-lubricating gold surface anti-coagulation coating structure NP 50 -SLIPS.

[0074] Example 2

[0075] (1) Take 20 μL of the 100 mM chloroauric acid solution prepared in Example 1 and apply it to a 1×1 cm 2 Example 1 After cleaning, the gold-plated surface is 1×1 cm 2 The gold-plated surface was completely covered and placed at room temperature for 10 minutes to fully perform in-situ reduction of chloroauric acid to form a micro-nano gold surface. The morphology of the micro-nano gold surface (SEM, two-dimensional AFM, and three-dimensional AFM) are shown in Figure 2. Figure 1c , Figure 2c , Figure 3c shown. Figure 1c , Figure 2c , Figure 3c It shows that after the gold-plated layer is modified in this step, its surface roughness is improved, and its arithmetic average roughness Ra = 41.9nm. After the gold-plated layer is modified in this step, a micro-convex dendrite surface coating is formed, forming a uniform and dense gold nanoparticle coating at the micro-nano level.

[0076] (2) In 1×1cm 2 20 μL of the fluorine-containing thiol solution prepared in Example 1 was applied on the surface of the micro-convex dendrite-shaped micro-nano gold to form a fluorine-containing thiol modified layer.

[0077] (3) In an environment of 80°C, perfluoropolyether was injected into a 1×1 cm 2 The micro-convex dendrite-shaped nano-gold surface containing the fluorinated thiol modified layer was placed for 48 hours, and then the gold surface was placed vertically to the horizontal plane for 12 hours to remove the excess perfluoropolyether, thereby obtaining a self-lubricating gold surface anti-coagulation coating structure NP 100-20 -SLIPS.

[0078] Example 3

[0079] (1) Take 50 μL of the 100 mM chloroauric acid solution prepared in Example 1 and apply it to a 1×1 cm 2 Example 1 After cleaning, the gold-plated surface is 1×1 cm 2The gold-plated surface was completely covered and placed at room temperature for 10 minutes to fully perform in-situ reduction of chloroauric acid to form a micro-nano gold surface. The morphology of the micro-nano gold surface (SEM, two-dimensional AFM, and three-dimensional AFM) are shown in Figure 2. Figure 1d , Figure 2d , Figure 3d shown. Figure 1d , Figure 2d , Figure 3d It shows that after the gold-plated layer is modified in this step, its surface roughness is improved, and its arithmetic average roughness Ra = 57.9nm. After the gold-plated layer is modified in this step, a dendritic surface coating is formed, forming a uniform and dense gold nanoparticle coating at the micro-nano level.

[0080] (2) In 1×1cm 2 20 μL of the fluorine-containing thiol solution prepared in Example 1 was applied on the surface of the dendritic micro-nano gold to form a fluorine-containing thiol modified layer.

[0081] (3) In an environment of 80°C, perfluoropolyether was injected into a 1×1 cm 2 The dendritic micro-nano gold surface with fluorinated thiol modified layer was placed for 48 hours, and then the gold surface was placed vertically to the horizontal plane for 12 hours to remove the excess perfluoropolyether, and the self-lubricating gold surface anti-coagulation coating structure NP was obtained. 100-50 -SLIPS.

[0082] In Examples 1-3, the arithmetic average roughness represents the average value of the absolute value of the height deviation of all measurement points on the sample surface relative to the reference plane. Ra can help quantitatively describe the smoothness or roughness of the surface. A high Ra value represents a high surface roughness and a large surface ups and downs. A low Ra value represents a smoother surface and a small surface ups and downs.

[0083] Comparative Example 1

[0084] (1) Clean the gold-plated surface. First, use anhydrous ethanol solution to ultrasonically treat the gold-plated surface for 10 minutes to wash away grease, dust and other impurities; then use deionized water to ultrasonically treat for 10 minutes to further clean the residual ethanol; finally, use a blast drying oven set to 80°C to dry the surface moisture.

[0085] (2) In an environment of 80°C, perfluoropolyether was injected into a 1×1 cm 2 After the cleaned gold-plated surface was placed for 48 hours, the gold surface was placed vertically to a horizontal plane for 12 hours to remove excess perfluoropolyether, thereby obtaining a self-lubricating anti-coagulation gold surface Au-SLIPS.

[0086] Platelet adhesion test

[0087] Platelet adhesion test before and after gold plating layer modification, the specific experimental operation process is as follows:

[0088] 1. The blood used in this experiment is fresh rabbit blood. Fresh rabbit blood was mixed with 3.8wt% sodium citrate solution at a ratio of 10:1, centrifuged at 3000 rpm for 15 min, and the supernatant was taken as platelet-rich plasma (PRP).

[0089] 2. The gold-plated layer before modification and the self-lubricating gold surface anticoagulation coating structure obtained in Example 1-3 were used as samples respectively; the samples were placed in a twelve-well plate, 100 ul of PRP was dripped on the surface of each sample, and the plates were placed in a 37°C incubator for incubation for 1 hour.

[0090] 3. Take out the incubated samples, wash them three times with PBS, and fix them with 2.5% glutaraldehyde at 4°C for 4 hours.

[0091] 4. Wash (wash three times with PBS to remove glutaraldehyde solution) and dehydrate (gradient alcohol 50%, 70%, 90%, 100% stepwise dehydration for 10 min / time).

[0092] 5. The dehydrated sample was subjected to gold spraying and observed by scanning electron microscope. Figure 4a , Figure 4b , Figure 4c , Figure 4d shown.

[0093] Figure 4a It shows that there are a lot of platelets adhering to the surface of the unmodified gold-plated layer; Figure 4b , Figure 4c , Figure 4d It shows that the surface of the self-lubricating gold surface anti-coagulation coating structure obtained in Examples 1, 2, and 3 is smooth and flat, with almost no platelet adhesion. This shows that the self-lubricating gold surface anti-coagulation coating structure obtained after the modification treatment in Examples 1, 2, and 3 has good anti-coagulation ability.

[0094] 6. The platelet adhesion area ratio (adhesion rate) of each sample was statistically analyzed by the image processing software ImageJ to obtain the quantitative analysis results of platelet adhesion before and after the gold-plating layer was modified; Figure 5 Specifically, each sample was subjected to 5 replicate experiments, and the mean and standard deviation were calculated (the error bar shown in the figure is the standard deviation); GraphPad Prism 8 software was used for statistical analysis and final chart production. Figure 5 It shows that the adhesion rate of the unmodified gold-plated layer surface is as high as 40%, while the adhesion rate of the self-lubricating gold surface anti-coagulation coating structure surface obtained in Examples 1, 2, and 3 is only less than 2%, indicating that the self-lubricating gold surface anti-coagulation coating structure obtained after the modification treatment in Examples 1, 2, and 3 has good anti-coagulation ability.

[0095] Anticoagulation persistence test

[0096] The self-lubricating gold surface anti-coagulation coating structures obtained in Examples 1-3 and Comparative Example 1 were respectively prepared into samples of 1 cm × 1 cm. The water contact angles on the sample surfaces were measured. The prepared samples were then ultrasonically treated in PBS (PH = 7.2-7.4) for different time periods (ultrasonic frequency of 40 kHz, ultrasonic power of 100 W), and the water contact angles on the sample surfaces were measured. The test results are shown in FIG. Figure 6 shown.

[0097] Figure 6 It is shown that after 30 minutes of ultrasound, the surface contact angle of comparative example 1 decreases significantly, and the oil injection layer is lost. The surface contact angles of Examples 1, 2, and 3 decrease slowly to varying degrees as the ultrasound time increases, but all remain at a relatively high level. It shows that the self-lubricating gold surface anti-coagulation coating structure surface obtained after the gold-plated layer is modified by Examples 1-3 has very good stability, the lubricating oil layer does not lose, and has a lasting anti-coagulation effect. Among them, the contact angle of Example 3 after 30 minutes of ultrasound is higher than that of other examples, and has the best stabilization effect.

Claims

1. A gold surface anticoagulation coating structure, comprising, from bottom to top, a micro-nano gold surface, a grafted modification layer and an anticoagulation layer; The grafted modification layer contains fluorine-containing thiol, and the fluorine-containing thiol is grafted on the surface of the micro-nano gold; The anticoagulant layer contains a lubricant.

2. The gold surface anticoagulation coating structure as claimed in claim 1, characterized in that: The fluorine-containing mercaptan is selected from one or more of 1H, 1H, 2H, 2H-perfluorodecanethiol, 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluoro-1-octanethiol, and 3,3,4,4,5,5,6,5,6-n-fluoro-1-hexanethiol.

3. The gold surface anticoagulation coating structure as claimed in claim 1, characterized in that: The lubricant is selected from one or more of perfluoropolyether, silicone oil, fluorinated lubricating oil, ionic liquid, and polyethylene glycol, preferably perfluoropolyether and / or fluorinated lubricating oil.

4. A method for preparing the gold surface anticoagulation coating structure according to any one of claims 1 to 3, comprising: (1) Coating the gold surface with chloroauric acid solution to obtain a micro-nano gold surface; (2) coating a fluorine-containing thiol solution on the surface of the micro-nano gold, allowing it to stand, and drying it to form a grafted modification layer; (3) placing the micro-nano gold surface containing the grafted modification layer in a lubricant, soaking it, taking it out, and placing it vertically to form an anti-coagulation layer.

5. The preparation method according to claim 4, characterized in that: In step (1), the gold surface is a gold-plated surface.

6. The preparation method according to claim 4, characterized in that: In step (1), The solvent of the chloroauric acid solution is pure water; or / and, The concentration of the chloroauric acid solution is 10 mM to 100 mM, preferably 50 mM to 100 mM; or / and, Each 1×1cm 2 The dosage of the chloroauric acid solution on the gold surface is 20 μL to 100 μL, preferably 20 μL to 50 μL.

7. The preparation method according to claim 4, characterized in that: In step (2), The solvent of the fluorinated thiol solution is selected from anhydrous ethanol, acetone or isopropanol; or / and, The concentration of the fluorine-containing thiol solution is 1-5M, preferably 2-3M.

8. The preparation method according to claim 4, characterized in that: In step (2), Standing time of more than 12 hours; or / and, The drying conditions are vacuum and room temperature, and the drying time is more than 1 hour.

9. The preparation method according to claim 4, characterized in that: In step (3), The soaking temperature is 60-80°C, the soaking time is more than 48 hours, and the vertical placement time is more than 12 hours.

10. Use of the gold surface anticoagulation coating structure as claimed in any one of claims 1 to 3 or the gold surface anticoagulation coating structure prepared by the preparation method as claimed in any one of claims 4 to 9 in medical devices.

Citation Information

Patent Citations

  • Lubricant-infused surface biosensing interface, methods of making and uses thereof

    CA3193411A1

  • Drag reduction superhydrophobic coating and preparation method thereof

    CN102492942A

  • Slippery liquid-infused porous surfaces and biological applications thereof

    CN103703085A

  • Liquid coating and preparation method and device thereof

    CN108950641A

  • Method for enhancing mixing performance of rotating packed bed based on liquid distributor with super-hydrophobic surface

    CN111659311A